(untitled) (Palíndromo, 2025)
In 1934, the Palácio de Cristal in Porto, hosted the First Portuguese Colonial Exhibition, an event designed to promote colonial endeavors and the supposed successes of the Portuguese Empire. Among its defining features were the exoticization of Black and racialized bodies - materialized in a "human zoo" - and the glorification of nationalist monuments throughout the city. Although ostensibly relegated to invisibility to avoid remembrance, these elements remain latent in the colonial imaginary that continues to shape present-day social relations. In 2020, at the same location, the Galeria Municipal do Porto launched the Programa de Incursão à Galeria (PING!), a mediation and education project that engages with this past as a subject of reflection, inviting individuals from diverse positionalities to challenge its supposed invisibility and its ongoing effects.This study offers a reflection on PING!, analyzing the disputes and negotiations involved in educational work within a site of memory, through the concepts of contact zone and agonistic conflict zone. Methodologically, the approach is grounded in episodic analysis, articulated through essayistic and narrative writing, based on situations recorded in field diaries during the observation of PING!’s activities. The reflection highlights how Portuguese whiteness emerges as a central axis of tension, often expressed through resistance and racist attitudes when confronted with historical responsibilities. The study concludes that engaging with this white racial discomfort constitutes a crucial task if educational practices are to move toward reparative gestures regarding the colonial past.